Causal Loop Diagram Rantai Pasok Semen di Kota Palangka Raya - Syarifah Aulia; Almuntofa Purwantoro (Jurnal Basement : Jurnal Teknik Sipil, 2024)
Project construction is a type of activity where time, resources, and costs are controlled and discussed to achieve a goal in the form of buildings or infrastructure. The construction of infrastructure and project construction activities require about 70-75% of the national cement consumption. The use of cement in Indonesia will increase in line with the growth of the national economy and the development of infrastructure and property. To balance rapid growth, Kota Palangka Raya needs infrastructure development. The goal of this research is to understand the shape of the Causal Loop supply chain of cement in Kota Palangka Raya. In the research process, data analysis techniques using dynamic system methods with Vensim software are used. This research uses primary data obtained from interviews with distributors and retail stores scattered in Kota Palangka Raya and secondary data obtained from literature reviews, including articles, books, and supporting research documents. The results of the Causal Loop supply chain of cement in Kota Palangka Raya show three cement brands, namely Gresik, Conch, and Tiga Roda, which are distributed in Kota Palangka Raya